A Review of Fabrication Options and Power Electronics for Flapping-Wing Robotic Insects. (4th March 2013) - Chen, Chen; Tang, Yichao; Wang, Haoyu; Wang, Yiding
Flapping-wing robotic insects are novel micro air vehicles (MAVs) inspired from biological insects in order to achieve a small size, high manoeuvrability and super remote ability. Such MAVs are centimetre scale flying robots with a number of applications, including exploration, environmental monitoring, rescue and reconnaissance. Due to the strict weight and power requirements of MAVs, the power electronics topologies need to be considered seriously. This paper describes state of the art power electronics topologies suitable for driving fl This -wing robotic insects. Comparisons are made in the resulting configurations of MAVs across several key metrics to estimate their performance. Discussion on the effect of performance gains in various power electronic topologies are abridged and presented.